Amidas halogenadas: reações de acoplamento e investigação in silico da atividade antimicrobiana - Montes, Ricardo Carneiro (2016)
This study aimed to prepare a collection of benzylamides to-halogenated derivatives of structurally related benzoic and cinnamic acids by coupling reactions with 4- (chlorine, bromine and fluro) benzylamines using the Benzotriazol-1-yloxy)tris(dimethylamino)phosphonium hexafluorophosphate (BOP) as coupling agent. All compounds prepared were subjected to antimicrobial testing the method broth microdilution, with the antimicrobial control gentamicin, amikacin, norfloxacin, penicillin and nystatin. Also, a study was conducted of quantitative structure-activity relationship (QSAR) using computational software like KNIME v. 3.1.0 and Volsurf v. 1.0.7. The study achieved the preparation of amides 22 and 10 derived ethers and esters of vanillic acid amide, with yields ranging from 29-89%, including 30 novel compounds in the literature and identified by spectroscopic methods such as Infrared and 1H and 13C Magnetic Resonance (NMR) as well as by high resolution mass spectrometry. The antimicrobial evaluation showed that eleven amides showed antifungal activity, an amide presented an antibacterial activity and no amide derivative of vanillic acid showed antimicrobial activity. The QSAR study showed that molecular descriptors related to hydrophobicity, hydrophilicity, pH change, energy interaction and energy difference as DRDRDR, DRDRAC, L4LgS, IW4 and DD2, respectively, influence the antifungal activity of haloamides. It follows that the NR14 amides (Gallic amide) and NR15 (vanillic amide) had considerable Minimum Inhibitory Concentrations (MIC) in antifungal essays, and NR4 (4-methoxycinnamic amide) in the antibacterial test, considered the most active antimicrobial. This result shows that spacer groups as double bond of cinnamic derivatives and addition of hydroxyls in the position para and methoxyl in the meta position on the aromatic ring of the amide enhance the antifungal activity.